Nepal’s Gender Policies: Achievements and Challenges - Rana, Bandana; Koirala, Samiksha (Nepal Public Policy Review, 2021)
Nepal has experienced extraordinary political and social changes in the last 25 years. Since the Constituent Assembly (CA) election in 2008, progress has been noted in increasing women’s access to literacy, education, and healthcare services. Despite significant gender reforms in policies and strategies, Nepali women continue to experience discrimination and violence mainly because of their gender. Drawing upon six different cases – constitutional and international framework, participation of women, women peace and security, sexual and reproductive health rights, gender-responsive budget and citizenship law – this paper highlights some of the achievements and gaps in the area of gender reform policies and practices. Methodologically, the study adopts document review and personal reflections of authors as the main source of information. The paper concludes with some key recommendations to address existing challenges and gaps of these selected policies/strategies.